La gestión de la calidad en Perú: un estudio de la norma ISO 9001, sus beneficios y los principales cambios en la versión 2015 - Lizarzaburu Bolaños, Edmundo R. (2016)
Considering the great importance of quality management at the present international juncture, this research reviews and analyzes the most important standard pertaining thereto, i.e. ISO 9001. In this paper, the origins of the term “quality” are established, as well as its evolution over time. It is defined by using the description of the family of standards. In addition, its structure and also the principles on which it is based were identified. Following the above and as an additional result of this work, the qualitative and quantitative benefits with which the standard provides companies registered with it are detailed. Finally, the main changes that the new ISO 9001:2015 revision will include are established.